Bibliometric Analysis of Employee Psychological Empowerment Studies: Trends, Gaps and Impacts Organizational - Josafat Gracia Ginting (International Humanity Advance, Business & Sciences, 2026)
Psychological empowerment has become an important concept in organizational behavior because it reflects employees’ perceptions of work meaning, competence, autonomy, and influence over work outcomes. In modern organizations, psychological empowerment is essential for improving employee motivation, engagement, creativity, well-being, and performance, especially in dynamic work environments. This study aims to conduct a bibliometric analysis of employee psychological empowerment studies in order to map the development of the field, identify dominant research trends, reveal research gaps, and analyze organizational impacts generated from existing studies. This research used a bibliometric approach. Data were collected from Google Scholar using Publish or Perish 8 and 35 articles published between 2020 and 2026 were selected for analysis. The data were exported in RIS and analyzed with VOSviewer through co-authorship and co-occurrence.  The findings show that psychological empowerment is the central keyword connecting research dominan themes, including work engagement, structural empowerment, employee creativity, transformational leadership, job satisfaction, employee well-being, ethical leadership, self-efficacy, job performance, psychological safety, and emotional exhaustion. The trend indicates a shift from structural and attitudinal studies toward performance, creativity, engagement, retention, and psychological safety. Research gaps remain in longitudinal studies, digital work contexts, cross-cultural comparisons, gender differences, and mental health interventions. Organizationally, psychological empowerment contributes to productivity, innovation, employee well-being, and long-term sustainability.